Clitics or Resumptives in Latakian Syrian Arabic Restrictive Relative Clauses (Journal of Hama University, 2025)
There is no consensus as to the nature of the overt element that appears at the site in the complement clause where the head of a restrictive relative clause is interpreted. Some argue that it is a clitic, while others argue that it is a resumptive. This paper tackles the relationship between clitics and resumption and the relevance of this to restrictive relative clause constructions in LSA. Some pieces of evidence are advanced to show that the clitic is not strictly the resumptive, and that it is pro which is the resumptive.
Keywords: clitics, resumptive, RRC, LSA